2014
DOI: 10.2337/dc14-0817
|View full text |Cite
|
Sign up to set email alerts
|

We Can Change the Natural History of Type 2 Diabetes

Abstract: As diabetes develops, we currently waste the first ∼10 years of the natural history. If we found prediabetes and early diabetes when they first presented and treated them more effectively, we could prevent or delay the progression of hyperglycemia and the development of complications. Evidence for this comes from trials where lifestyle change and/or glucose-lowering medications decreased progression from prediabetes to diabetes. After withdrawal of these interventions, there was no “catch-up”—cumulative develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 78 publications
1
61
0
Order By: Relevance
“…Modification of lifestyle factors is therefore an important strategy for reducing both the incidence of type 2 diabetes and subsequent complications. Several randomized clinical trials such as the Chinese Da Qing IGT and Diabetes Study, the Finnish Diabetes Prevention Study (DPS), and the U.S. Diabetes Prevention Program (DPP) have demonstrated that effective lifestyle intervention strategies (dietary modification and enhanced physical activity) can prevent or delay the progression to type 2 diabetes among high-risk adults with impaired glucose tolerance (15). Studies including the Da Qing IGT and Diabetes Study provided evidence suggesting that for subjects with impaired glucose tolerance, the more insulin resistance there is, the less benefit there is in preventing progression to diabetes with lifestyle change alone despite significant benefits in insulin sensitivity with lifestyle modification (16).…”
mentioning
confidence: 99%
“…Modification of lifestyle factors is therefore an important strategy for reducing both the incidence of type 2 diabetes and subsequent complications. Several randomized clinical trials such as the Chinese Da Qing IGT and Diabetes Study, the Finnish Diabetes Prevention Study (DPS), and the U.S. Diabetes Prevention Program (DPP) have demonstrated that effective lifestyle intervention strategies (dietary modification and enhanced physical activity) can prevent or delay the progression to type 2 diabetes among high-risk adults with impaired glucose tolerance (15). Studies including the Da Qing IGT and Diabetes Study provided evidence suggesting that for subjects with impaired glucose tolerance, the more insulin resistance there is, the less benefit there is in preventing progression to diabetes with lifestyle change alone despite significant benefits in insulin sensitivity with lifestyle modification (16).…”
mentioning
confidence: 99%
“…a-GIs seem to be somewhat weaker than metformin and DPP-4i to suppress FPG. The latter two drugs, metformin and DPP-4i, seem to be more preferable than the others, but it is necessary to check for a longer period to confirm their true efficacy also on the fate of T2DM [56]. It is possible that a-GI primarily inhibits post-prandial blood glucose and their effect on FPG may be rather indirect.…”
Section: Discussionmentioning
confidence: 96%
“…The prevalence of prediabetes is 50.1%, accounting for a total of 493.4 million people in China [2], and 70.7% of those with prediabetes had IGT [3] and form an important high-risk target group for intervention aimed at preventing T2DM [4,5]. Current guidelines recommend that IGT patients undergo lifestyle modifications, which have been shown to be effective for reducing the incidence of T2DM [6][7][8].…”
Section: Introductionmentioning
confidence: 99%